From Arab Spring to regional reset: Saudi-Iranian rivalry and strategic contestation in the Gulf (2011–2023) - Albarasneh, Ayman (Frontiers in Political Science, 2025)
This paper analyzes the Saudi-Iranian rivalry between 2011 and 2023 and its implications for Gulf regional security. It shows that the rivalry operates simultaneously at state, sub-state, and symbolic levels, reinforced through proxy conflicts, sectarian mobilization, and competing identity narratives. While the 2023 diplomatic breakthrough suggested progress, the findings confirm that the structural and ideological foundations of the rivalry remain unresolved. Positioned within a descriptive-analytical, interpretive framework, the research applies process tracing to examine key geopolitical events, including the Arab Spring, the Yemen war, the U.S. withdrawal from the JCPOA, and the 2023 China-mediated normalization. These events are viewed as part of a continuous geopolitical process shaped by power structures, domestic politics, and identity-driven strategies. The study integrates neorealism, offensive realism, and constructivism to provide a multi-dimensional explanation of the rivalry. While neorealism and offensive realism explain material interests and strategic behavior, constructivism highlights the role of identity, ideology, and sectarian narratives. A hybrid neorealist framework is proposed to incorporate non-state actors and symbolic tools of influence, reconciled methodologically through layered process tracing with explicit rules for weighing competing theoretical predictions. This theoretical approach helps explain both external behavior and internal motivations. The rivalry operates at state, sub-state, and symbolic levels, reinforced through proxy conflicts and religious mobilization. Although the 2023 diplomatic breakthrough suggests progress, the structural and ideological foundations of the rivalry remain unresolved. This research addresses a critical gap by combining theories and linking them to recent regional events. Policy recommendations include a formal dialogue platform between Gulf states and Iran, confidence-building measures, and a regional security charter. By combining theory, regional analysis, and policy insight, the study contributes to ongoing debates on Gulf security and offers practical ideas for future stability.